2010
DOI: 10.2319/052207-243.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical photography vs digital video clips for the assessment of smile esthetics

Abstract: The hypothesis cannot be rejected. A significant positive correlation was noted between Smile Mesh measurements obtained from smiles captured by clinical photography and those captured with digital video clips. This supports the conclusion that a standard digital photograph appears to be a valid tool for analysis of the posttreatment smile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 7 publications
0
41
0
2
Order By: Relevance
“…It has been noted that standardized digital videography provides the clinician with a wider range of images for selecting the parameters of lip-tooth relationship during facial animation, and that it is possible to select matching images at different time points from these multiple frame galleries to effectively compare the “same” posed social smile. Undeniably, error is associated with selection of the appropriate still frame representing the posed social smile; similarly, a photograph taken of the smile has error associated with it 28. Schabel et al28 found that there is no clinically significant difference between the images of smiles of subjects captured by clinical photography and the smiles of the same subjects obtained from digital video clips.…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that standardized digital videography provides the clinician with a wider range of images for selecting the parameters of lip-tooth relationship during facial animation, and that it is possible to select matching images at different time points from these multiple frame galleries to effectively compare the “same” posed social smile. Undeniably, error is associated with selection of the appropriate still frame representing the posed social smile; similarly, a photograph taken of the smile has error associated with it 28. Schabel et al28 found that there is no clinically significant difference between the images of smiles of subjects captured by clinical photography and the smiles of the same subjects obtained from digital video clips.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible criticism might be that obtaining a valid and reproducible smiling image on a single photographic image might be difficult (Ackerman and Ackerman, 2002); however Schabel and colleagues (Schabel et al, 2010) have shown that smile assessments undertaken from standard digital photographs are similar to those obtained from a captured digital video clip.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of standardization and the inability to capture images accurately are 2 limiting factors. 33,34 Photography was expected to produce results similar to this study. However, videography might have an additional diagnostic value when patients' oral functions are evaluated.…”
Section: Maxillary Anterior Overjetmentioning
confidence: 52%